Rebuilding Land Policy as a Base of Exploitation Right Preventing on the Land for Industrialization: Study on Mapping and Land Using in Social Function - Handoko, Widhi; Negara, Purnawan D (International Conference of Moslem Society, 2018)
Policies in agrarian and natural resources is very close with economic liberalization that is the land exploitation for industrialization. The pressure of economic flows affects the political alignment of the economic power, so the bureaucratic system becomes weak. Das sollen concern with the industry is regulated with UU No. 3 year 2014 about Industrial and with PP No. 142 year 2015 about Industrial Area. The industrial provisions related to land rights are regulated in PP. 13 year 1995. According to Agrarian rules/Kep. BPN RI No. 2 year 1999, to attain the industrial permit, the applicant must obtain the location permit first which published by the Agrarian Office. Location permit is a license granted to a company to acquire the necessary land for investment, and it can be used as a license of replacement rights for using the land investment purposes. The government is very confident with the rules it makes, and does not focus on the economic impacts of liberalization that arise. The neglect on the environmental impacts to land rights exploitation, either directly or indirectly, has formed a "social system" that will interact in society, in the form of "system of expectations", so it becomes a very complex interaction which eventually emerges egocentric of human nature. A mutual relationship exists among the interested parties (it can be either positive or negative excess). Ultimately on behalf of the bureaucracy, the economic liberalization is born that puts the land on the economic function and market mechanisms, and keep away the social function of land rights from the concrete meaning of social justice.